2009
DOI: 10.1371/journal.pntd.0000462
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Age-Structured Model for Trachoma Transmission Dynamics, Pathogenesis and Control

Abstract: BackgroundTrachoma, the worldwide leading infectious cause of blindness, is due to repeated conjunctival infection with Chlamydia trachomatis. The effects of control interventions on population levels of infection and active disease can be promptly measured, but the effects on severe ocular sequelae require long-term monitoring. We present an age-structured mathematical model of trachoma transmission and disease to predict the impact of interventions on the prevalence of blinding trachoma.Methodology/Principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 37 publications
1
101
0
Order By: Relevance
“…This resulted in a more acute change in SCR, as has been demonstrated in malaria modelling exercises 45,46 . Previous trachoma modelling studies suggest that an individual may require upwards of 100 lifetime ocular Ct infections in order to develop TT 47 , so even a modest reduction in transmission may have significant public health implications and reduce the future incidence of TT.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a more acute change in SCR, as has been demonstrated in malaria modelling exercises 45,46 . Previous trachoma modelling studies suggest that an individual may require upwards of 100 lifetime ocular Ct infections in order to develop TT 47 , so even a modest reduction in transmission may have significant public health implications and reduce the future incidence of TT.…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive studies should consider the influence of partial acquired immunity (Liu et al ., 2013), chemoprophylaxis in susceptible persons, seasonality in transmission (Lee et al ., 2005), age-structure in the host population (Bailey et al ., 1999; Lietman et al ., 1999; Gambhir et al ., 2009), bacterial load (Shattock et al ., 2015), case importation, and other ecological or epidemiological factors (Lietman et al ., 1999). Changes in population size, structure and distribution need to be reflected in a long-term MDA program.…”
Section: Discussionmentioning
confidence: 99%
“…This article discussed the proposal that there might be an Allee effect operating for trachoma, an idea based on the observation that the community prevalence level in a mass drug administration (MDA) field trial had held steady over a year after the administration of drug to the population (Solomon et al, 2004). This observation stood in contrast to the predictions of modelling and other posttreatment observational studies which found re-emergence of infection and disease to be the most likely outcome (Gambhir et al, 2010a(Gambhir et al, , 2009Liu et al, 2014;Burton et al, 2005;West et al, 2005). The proposed mechanisms for an Allee effect for trachoma include reductions in bacterial genotypic diversity leading to more effective immune responses from the host population, and a dose-dependent effect in which lower community prevalence leads to lower average chlamydial load and lower probability of transmission per contact.…”
Section: Allee Effects and Disease Eliminationmentioning
confidence: 99%